2016
DOI: 10.1073/pnas.1508932113
|View full text |Cite
|
Sign up to set email alerts
|

Dominant, open nonverbal displays are attractive at zero-acquaintance

Abstract: Across two field studies of romantic attraction, we demonstrate that postural expansiveness makes humans more romantically appealing. In a field study (n = 144 speed-dates), we coded nonverbal behaviors associated with liking, love, and dominance. Postural expansivenessexpanding the body in physical space-was most predictive of attraction, with each one-unit increase in coded behavior from the video recordings nearly doubling a person's odds of getting a "yes" response from one's speed-dating partner. In a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…She tried to maintain a certain style but had to adjust her attire depending on the changes in outside and inside temperatures during the year. Another possible limitation of our study is that our study sample-although similar in size to samples used in similar studies that worked with microanalysis of behaviour (Farley, 2014;Gonzaga et al, 2001;Hall & Xing, 2015;Renninger et al, 2004;Vacharkulksemsuk et al, 2016;Van der Meij, Almela, Buunk, Almela, Buunk, Fawcett, & Salvador, 2011)-was still relatively small and may have failed to confirm the statistical significance of effects, which are of merely a moderate strength. Aside from that, the use of one single experimenter who conducted all the interviews with all test couples may have led to some experimenter-specific effects.…”
Section: Discussionmentioning
confidence: 97%
“…She tried to maintain a certain style but had to adjust her attire depending on the changes in outside and inside temperatures during the year. Another possible limitation of our study is that our study sample-although similar in size to samples used in similar studies that worked with microanalysis of behaviour (Farley, 2014;Gonzaga et al, 2001;Hall & Xing, 2015;Renninger et al, 2004;Vacharkulksemsuk et al, 2016;Van der Meij, Almela, Buunk, Almela, Buunk, Fawcett, & Salvador, 2011)-was still relatively small and may have failed to confirm the statistical significance of effects, which are of merely a moderate strength. Aside from that, the use of one single experimenter who conducted all the interviews with all test couples may have led to some experimenter-specific effects.…”
Section: Discussionmentioning
confidence: 97%
“…There are currently over 33 published studies on the positive effects of expansive (versus contractive) body postures on increasing subjective feelings of power, pain, hunger and romantic attractiveness [113,114]. In their original study, Carney et al [115] also found an embodiment effect on increasing risk taking, as well as a biological effect of increasing the aggressive hormone testosterone and in reducing the stress hormone cortisol.…”
Section: The Embodied Model Of Cognition and Emotionmentioning
confidence: 99%
“…For instance, both smiling and laughing have been reported to reflect the degree of attraction to the other person, and subsequently cause the other to be attracted to the person expressing the smiles and laughter (5)(6)(7). Similarly, head nods and open body postures are associated with more self-reported feelings of love among newly met and long-term committed relationship partners (8)(9)(10). In addition, dominant body posture, direct eye contact (5,11,12), increased skin conductance and heart rate responses have all been linked to the perception of more attractive, opposite-sex targets (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the current literature suggests that attraction emerges from the dynamic exchange of verbal and nonverbal signals (5,(9)(10)(11)22), yet the necessary empirical and analytic tools to directly address this hypothesis were not available until recent times. Consequently, the direct link between nonverbal behavior, physiology and attraction has never been directly verified.…”
Section: Introductionmentioning
confidence: 99%